Depicting Epistemological Obstacles in Understanding the Concept of Sequence and Series - Samsul Maarif; Krisna Satrio Perbowo; Rahmat Kusharyadi (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aimed to discover epistemological obstacle on secondary students to solve sequence and series problems based on three indicators, there are a conceptual obstacle, procedural obstacle, and operational technique obstacle. This study was descriptive with qualitative research approaches. Data were collected with the test and interview method. The subjects in this study are students of SMP Negeri 86 Jakarta class VIII based on the errors seen from the diagnostic tests that had been tested. The analysis was done by giving written tests which are essay and interview formatted. Results on analysis showed that: (1) Conceptual obstacle, obstacle that was experienced by students are: students considered that a pattern was said as a numeral pattern because they own odd numeral pattern and own 2,2,2 of difference; were not able to find exact pattern within the problem; considering that Fibonacci numeral sequence was a pattern that form prime numeral pattern; were not able to differ the concept of arithmetics and geometry sequence; were not able to understand the concept of first quarter on arithmetics sequence; error when interpreted the meaning of problems; were not able to intepret what was given on mathematics model; interpreting sum of the first 20 quarters with sequences which own the 20th quarter; and interpreting sum of the first 20 quarters with the 20th quarter; (2) While on procedural obstacle, obstacle that was experienced are: interpreting numeral pattern if they own their pair; error on determining multiplication or difference; and applying formulas incorrectly; (3) Last on operasional technique obstacle, obstacle that was experienced are error on calculation and using sign and symbol mathematics incorrectly.